Digital Populism in Islamic Da’wah: A Rhetorical Analysis of @iqdammuhammad’s Instagram Communications - Siti Waqiatul Hasanah; Widadi; Danil Kiromah; Syifa Aghniya Ridwan; Abdullah Sattar (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study discusses the process of public communication in da'wah conducted through the Instagram account @iqdammuhammad, focusing on the application of Aristotle's rhetorical strategies, which include ethos, pathos, and logos. The background of this research stems from the phenomenon of persuasive communication strategies in accordance with the characteristics of social media and audience preferences, particularly among young people. This study aims to analyze how these three rhetorical elements are implemented in Gus Iqdam's da'wah content and how their application affects the effectiveness of public communication in disseminating religious messages. The research method used a descriptive qualitative approach with content analysis techniques on several posts that represent the preaching communication strategy on the account. The results of the study show that ethos is reflected through scholarly credibility, a religious image, and consistency in delivering messages. Pathos is seen through a communicative delivery style, use of humor, and engaging visuals, creating an emotional connection with the audience. Logos appears through arguments based on religious texts and rational explanations relevant to daily life. The integration of these three rhetorical aspects contributes to increased audience engagement and the cognitive and affective reception of preaching messages. In conclusion, the study affirms that utilizing Aristotle's rhetorical strategies in digital preaching can enhance the effectiveness of public communication on Instagram.